2011
DOI: 10.1111/j.1469-8986.2011.01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Scan patterns when viewing natural scenes: Emotion, complexity, and repetition

Abstract: Eye movements were monitored during picture viewing and effects of hedonic content, perceptual composition, and repetition on scanning assessed. In Experiment 1, emotional and neutral pictures that were figure-ground compositions or more complex scenes were presented for a 6 s free viewing period. Viewing emotional pictures or complex scenes prompted more fixations and broader scanning of the visual array, compared to neutral pictures or simple figure-ground compositions. Effects of emotion and composition wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
94
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 35 publications
23
94
1
1
Order By: Relevance
“…Regarding oculomotor measures of attention, both pleasant and unpleasant pictures attract more fixations and broaden scanning of the array (Bradley, Houbova, Miccoli, Costa, & Lang, 2011), and increase pupillary dilation (Bradley, Miccoli, Escrig, & Lang, 2008), relative to neutral pictures. In this context, we have made some contributions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding oculomotor measures of attention, both pleasant and unpleasant pictures attract more fixations and broaden scanning of the array (Bradley, Houbova, Miccoli, Costa, & Lang, 2011), and increase pupillary dilation (Bradley, Miccoli, Escrig, & Lang, 2008), relative to neutral pictures. In this context, we have made some contributions.…”
Section: Discussionmentioning
confidence: 99%
“…When shown a pleasant or unpleasant image in a pair with a neutral image, viewers attended more quickly and show longer fixation times for the emotional images [Nummenmaa et al 2006]. In studies of single images, participants similarly had more fixations and longer total gaze durations on pleasant and unpleasant emotional images than on neutral images [Bradley et al 2011]. Niu and colleagues [2012] performed an in-depth comparison of visual and emotional salience models and found that emotional salience overrides visual salience in driving eye movements.…”
Section: Related Workmentioning
confidence: 94%
“…This technique has also been used to measure emotional arousal. For example, Bradley, Miccoli, Escrig, and Land (2008) found that pupil size increased when students looked at emotionally charged pictures and that these changes correlated with traditional physiological measures of arousal such as skin conductance. Educational applications of this method are rare.…”
Section: Assumption 4-pupil Sizementioning
confidence: 94%